Experimental and numerical investigation of swirl enhancing grooves on the flow and combustion characteristics of a DI diesel engine. (15th November 2016) - Prabhakaran, P.; Ramesh, P.; Saravanan, C.G.; Loganathan, M.; James Gunasekaran, E.
Abstract: This paper discusses the results of numerical and experimental investigations carried out with swirl enhancing modifications on a DI diesel engine. Six tangential holes on each piston with diameters of the hole varying from 2, 2.5, 3 and 3.5 mm are made in the piston with suitable inclinations with respect to the cylinder axis. Numerical investigations are carried out at full load condition with the modified engine piston. Results reveal that the tangential hole of 2.5 mm produce a better combustion and higher pressure. The swirl motion as well as kinetic energy increases with the increasing hole diameters. The piston with 2.5 mm hole produce a highest performance improvement while the pistons with higher diameter than 2.5 mm produce a slightly lower performance. While the increase in diameter increases the flow field characteristics like swirl, the performance declines beyond 2.5 mm. Considering the performance point of view a 2.5 mm diameter hole provides better combustion and hence highest pressure for the same fuel injected. The other holes like 2.5 mm, 3 mm and 3.5 mm have slightly higher soot emission. Since numerical results proved that 2.5 mm provides a better performance, only three tangential holes 2 mm, 2.5 mm and 3 mm were taken up for experimental investigation. Of all the modifications the 2.5 mm piston gives better performance with higher brake thermal efficiency and lowest soot emission. Highlights: Swirl enhancing tangential holes six in numbers are drilled in each piston. The hole diameters varies between 2.0 mm and 3.5 mm. The holes were made in such a way that the squish air enters the bowl through the holes into the bowl tangentially. Numerical and experimental investigations were conducted to determine an optimum hole size. Performance improves until certain optimum diameter (2.5 mm) tangential hole and then the performance deteriorates.